THE ROLE OF UNIVERSITIES IN THE DEVELOPMENT OF ENTREPRENEURIAL SKILLS OF STUDENTS - Evgeniy A. Deviatkin; Svetlana V. Laskovets (Статистика и экономика)
The article discusses the conceptual issues of formation of the competence approach, foreign experience of study competencies, the introduction of competence-based approach in the Russian universities in the transition to the GEF, presented requirements of the labor market to a graduates , found the place and role of entrepreneurial competencies of students in the recruitment process, shown teaching methods forming entrepreneurial skills.